Bridging the gap: unleashing the power of non-core departments through interdepartmental collaboration - Ren, Siyu; Wang, Yile (Frontiers in Psychology, 2024)
Traditional research on firm performance has predominantly emphasized the role of key departments, often underestimating the potential contributions of non-core departments.This study redresses this oversight by investigating the impact of non-core departments on firm performance. Utilizing a comprehensive 20-year dataset from Chinese A-listed firms and employing the endogenous growth model, we scrutinize the influence of non-core departments on enterprise productivity and organizational growth. Our findings underscore that non-core departments significantly enhance firm performance. Furthermore, we observe a negative coefficient of the interaction term, implying the presence of diminishing returns to scale when amalgamating department diversity with firm knowledge. This suggests that while both department diversity and firm knowledge independently contribute positively to firm performance, their conjoined effect does not necessarily induce a proportionally amplified impact. Moreover, we found that factors such as the company's equity structure, market environment, and the age and education level of executives may moderate the impact of departmental diversity on firm performance. This study enriches the literature by spotlighting the potential of non-core departments in propelling firm success and underlines the imperative for strategies that cultivate interdepartmental collaboration. The implications of these findings propose that firms can leverage the potential of non-core departments for sustainable growth, offering a fresh perspective for future research in organizational development.